Local Wisdom on the Use of Minangkabau Proverbs Meaning Satire by the Minangkabau Community in Medan - Bahri, Syamsul (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
The objective of this research is to know more aboutÃ‚Â the complete description of Local Wisdom on the Use of the Minangkabu Proverb Meaning Satire by the Minangkabau Community in Medan. This research uses descriptive qualitative method which can be interpreted as a problem solving procedure that is investigated by describing the state of the object of research at the present time based on the facts that appear or as they are.The sample of this research limitedÃ‚Â to 8 (eight) Minangkabau informants from the four Kotamatsum Kelurahan. After conducting this research, it was found that the use of the Minangkabau Proverb having meaningful satire by the Minangkabau Society in Medan was more dominant in the Social and Cultural context. This shows that the Minangkabau Society in social interaction with each other always uses a sentence that is decorated, especially the use of the proverbial Minangkabau meaning satire which aims at providing input, criticism and advice in accordance with religious aspects, customs and tradition which are held firmly by the Minangkabau community.